Lessons Learned In Distributing Videotapes In Demand - John R. Brooks (Journal of Applied Communications, 1991)
The Louisiana State University Agricultural Center developed a series of videotapes on farm-raised alligators, catfish, crawfish, and redfish, using special state grant funds.